Inactivation and Phosphorylation of Kanamycin by Drug-resistant Staphylococcus aureus - Doi, Osamu (1968)
The cell-free system of clinical isolates of drug-resistant Staphylococcus aureus inactivated kanamycin, and the inactivated product was identified with kanamycin-3′-phosphate, in which the C-3-OH of the 6-amino-6-deoxy-d-glucose moiety of kanamycin was phosphorylated.